The effectiveness of augmented reality technology in developing visual thinking skills in the field of technology for tenth grade students in North Gaza Governorate - Awad, Monir Said; Abu Elba, Ahmed Mohamed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to reveal the effectiveness of augmented reality technology in developing visual thinking skills in the technology subject for tenth graders in North Gaza Governorate. To achieve the goal of the study, the quasi-experimental approach was used. As for the study tool, it consisted of a visual thinking test consisting of (25) questions. The study sample consisted of (80) students from the tenth-grade students at Othman Ibn Affan Secondary School for Boys affiliated to the North Gaza Education Directorate; Of them (40) students who studied through augmented reality technology, and they represent the experimental group, and (40) other students who studied in the normal way, and they represent the control group. The results of the study reached the total scores of the experimental group and the scores of the control students in the application, the sum of the scores of the experimental group and the control group of students, the adjusted gain for Black, where the percentage calculated for the effectiveness of the reinforcer according to Black’s equation (1.93). And then the costs of studying in universities.